Legionella control in water systems using copper and silver ion generation systems - Bedford, Birgitta (Cranfield University, 2012)
Legionella can cause human disease which can be fatal. Routine monitoring for Legionella in water systems is not recommended by UK authorities. Evidence of the efficacy of control modalities against Legionella in these water systems is, therefore, not available. Although studies have been conducted with copper and silver ionization on its efficacy against Legionella and on its value in reducing hospital-acquired legionellosis, little evidence of its efficacy is available from routine monitoring data. This study demonstrates the efficacy of copper and silver ionization against Legionella in water systems of 10 hospitals from data obtained from routine monitoring for Legionella, copper and silver. The inefficiencies of maintaining temperatures above 50ºC at hot outlets and below 20ºC at cold outlets, as recommended by UK authorities for controlling Legionella in water systems, is also demonstrated from the data obtained from routine monitoring for Legionella and temperatures. The futility of maintaining hot temperatures above 50ºC and then to reduce them to temperatures that do not present a risk of scalding is also demonstrated from the data obtained. This efficacy of copper and silver ionization and inefficiency of maintaining temperatures at 50ºC against Legionella was demonstrated as well in novel model rigs, built to simulate a typical water system of a small hospital, by data obtained from Legionella, copper, and silver analysis, and temperature recordings. The differences in biofilm formation and Legionella growth on the surfaces of copper, polyethylene, and synthetic rubber, which are commonly used plumbing materials, were also examined in the model rigs as well as with a Robbins device. These studies indicated that copper is not as biocidal as previously reported in other studies, and gave similar results to polyethylene, which previously been shown to promote biofilm development. Synthetic rubber, however, showed to promote biofilm production and should not be used as a plumbing material.